Broadly reflexive relationships, a special type of hyperbole, and implications for metaphor and metonymy. - Barnden, John (Metaphor & Symbol)
As the author has previously argued, a statement of form "Y is X" can often be taken as hyperbolic for a notably high degree of likeness between Y and X, or, instead, as hyperbolically stating how important Y is as a part of X. The present article goes further and argues that these types of hyperbole, as well as various others, are just special cases of reflexive hyperbole, a style that appears not previously to have been explored in its own right. The article therefore serves to introduce this style and to unify under it various more specific, disparate-seeming types of hyperbole, revealing their deep similarity. They all rest in a uniform way on a special property that some relationships have, namely of being reflexive in a broadened sense. The relationship of likeness is reflexive in the standard sense that any entity bears the relationship to itself with maximum possible strength. But some other relationships of interest in this article are only reflexive in a broader way that relaxes these universality and maximality requirements to an extent. The article also explains how reflexive hyperbole about likeness is a novel addition to the theory of metaphor, involving a distinctive interpretative process with special effects, and how reflexive hyperbole about part importance is not reducible to whole-for-part metonymy, because the latter does not systematically access sufficiently important parts. In addition, the article briefly considers the defaultness or otherwise of reflexive hyperbolic interpretations.